2021
DOI: 10.3389/fimmu.2021.635015
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Lysine Levels Improved Antioxidant Capacity and Immunity via the TOR and p38 MAPK Signaling Pathways in Grass Carp, Ctenopharyngodon idellus Fry

Abstract: An 8-week rearing trial was designed to appraise the dietary lysine levels on intestinal antioxidant capacity and immunity of grass carp fry. Six practical diets were prepared with graded levels of lysine (1.44, 1.79, 1.97, 2.44, 2.56 and 2.87% dry matter), and these diets were fed to grass carp fry. The results showed that the activities of intestinal antioxidant factors including catalase and glutathione peroxidase were markedly improved by the 2.44% dietary lysine compared with the control diet (1.44% dieta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 68 publications
(76 reference statements)
3
20
0
Order By: Relevance
“…Similar statements were seen in other fish species such as silveryblack porgy, S. hasta (Yaghoubi et al, 2018) and grass carp, C. idella (Huang et al, 2021;Li et al, 2014). Fazio et al (2017) in their studies on flathead mullet, Mugil cephalus and gilt-head sea bream, Sparus aurata reported that the oxidative status and relationship between total oxidant status (TOS) and total antioxidant capacity (TAC) in serum are presumably reliant upon the fish species and are influenced by different feeding habits and the presence of appropriate nutrient.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Similar statements were seen in other fish species such as silveryblack porgy, S. hasta (Yaghoubi et al, 2018) and grass carp, C. idella (Huang et al, 2021;Li et al, 2014). Fazio et al (2017) in their studies on flathead mullet, Mugil cephalus and gilt-head sea bream, Sparus aurata reported that the oxidative status and relationship between total oxidant status (TOS) and total antioxidant capacity (TAC) in serum are presumably reliant upon the fish species and are influenced by different feeding habits and the presence of appropriate nutrient.…”
Section: Discussionsupporting
confidence: 69%
“…Several past workers have suggested that dietary Lys has a key role in the regulation of antioxidant response in fish, which could influence the actions of different antioxidant enzymes (Huang et al, 2021;Li et al, 2014). Superoxide dismutase (SOD) is treated as one of the main antioxidant defence pathways, which plays a significant part in disease resistance and immunity (Li et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the inclusion of dietary phospholipids significantly decreased the expression of rela in a quadratic manner, followed a similar pattern with that of the proinflammatory cytokines. Moreover, nf-κb is a downstream target of the p38 MAPK signaling pathway, which is involved in the regulation of inflammation in mammals ( 22 ) and is suggested to influence the intestinal immune function of grass carp ( 24 , 74 ). In the present study, the transcription of p38 mapk , mapk 13 and mapk 14, was repressed with the inclusion of dietary phospholipids.…”
Section: Discussionmentioning
confidence: 99%
“…The nuclear factor kappa B (Nf-κB), a downstream target of the p38 MAPK signaling pathway, is a major signaling molecule in the regulation of cytokines production ( 23 ). Therefore, it has been suggested that, in teleosts, the p38 MAPK/Nf-κB pathway participates in the regulation of inflammation response ( 20 , 24 ). However, it is yet unclear whether dietary phospholipids can alleviate the intestinal inflammation response in fish larvae through the p38 MAPK/Nf-κB pathway.…”
Section: Introductionmentioning
confidence: 99%